Phase evolution and microwave dielectric properties of (Ca/Sr)Nd4Ti5O17–based ceramic systems. (25th September 2019) - Muhammad, Raz; Khan, Sohail; Hussain, Fayaz; Khesro, Amir
Abstract: x ANd4 Ti5 O17 –(1- x )Ca5 LaTi4 NbO17 (A = Ca, Sr; x = 0, 0.5, 0.6, 0.7) and 0.75ANd4 Ti5 O17 –0.25Ca0.6 La0.267 TiO3 (A = Ca, Sr) ceramics were processed via solid state sintering route. Phase analysis of the samples revealed that both phases remained un-reacted and were present in the solid solution. Microstructural analysis of the Sr-based samples showed porosity in the samples which significantly influenced the relative permittivity and quality factor of the sintered product. SrNd4 Ti5 O17 (SNT) and CaNd4 Ti5 O17 (CNT) exhibited ε r = 41, Q × ƒo = 10698 GHz and τ f = −119 ppm °C −1, and ε r = 42, Q × ƒo = 118260 GHz and τ f = −125 ppm °C −1, respectively. τ f of these samples was tuned by making their solid solution with Ca5 LaTi4 NbO17 (CLTN) and Ca0.6 La0.267 TiO3 (CLT), having high positive τ f, previously reported by the author. A good combination of microwave dielectric properties was achieved for the 0.7SNT–0.3CLTN sample i.e. ε r = 50, Q × ƒo = 4953 GHz and τ f = −10 ppm °C −1 . In the case of 0.7CNT–0.3CLTN, ε r = 46 and Q × ƒo = 5801 GHz were observed but had a relatively low τ f = −54 ppm °C −1 . Similarly, 0.75SNT–0.25CLT and 0.75CNT–0.25CLT ceramics exhibited ε r = 45.6 and 44, Q × ƒo = 6320 and 6234 GHz, τ f = +12 and −15 ppm °C −1, respectively.